Comparative assessment of groundwater quality in Kokrajhar, India - Yachang Omo; Swdwmsri Brahma; Avijit Paul (The Holistic Approach to Environment, 2024)
A study was carried out to analyse and compare the quality of groundwater in Kokrajhar during the pre- and post-monsoon seasons. Kokrajhar is experiencing a significant population growth and urbanisation. Groundwater is vital for the daily activities and consumption of the local population. In order to meet the needs of the local population, it is crucial to evaluate the quality of groundwater. The study involved the collection of groundwater samples from 20 different locations during the pre- and post-monsoon periods. Tests were conducted on groundwater samples to analyse 10 different test parameters. Sample points were located using geographical information system (GIS) and contour maps were generated to represent different test parameters. The assessment of groundwater quality was determined using two different methodologies: the Weighted Arithmetic Index (WAI) method and the Canadian Council of Ministers of the Environment Water Quality Index (CCME WQI) method. The results obtained by both methods were compared. Minor to significant variations in various test parameters were observed during analysis of pre- and post-monsoon groundwater samples.